Blockchain for medical research : accelerating trust in healthcare - Sean T. Manion; Yaël Bizouati-Kennedy (New York : CRC Press, 2020)
"It takes 17 years on average to bring new health ideas into evidence-based clinical practice. The growing replicability crisis in science further delays these "new miracles." Blockchain can improve replicability and hasten the knowledge translation process. This book is about science, its value to our health, and how we can use blockchain to improve its quality and impact. The book will look at science and medicine from an insider's perspective, and describe the processes, successes, shortcomings and opportunities for advancement for the lay audience. It will give the reader a non-technical look at the emerging world of blockchain technology; what it is, where it is useful, and how it can improve science and health. It will lay out a roadmap for this application to transform how we develop knowledge about disease and accelerate cures to improve our lives. In the first part, the authors look at science as a process and how this drives advancement in medicine. They'll then shed a light on some of science's shortcomings, including the reproducibility crisis and problems with misaligned incentives (i.e. publish or perish). The book applies a breakdown of critical components to the functional steps in the scientific process and outlines how the open science movement is looking to improve these.
Keywords: BUSINESS & ECONOMICS Information Management; Delivery of Health Care economics; Biomedical Research economics